Public expenditure on investments and reduction of regional poverty in Peru, period 2009-2018 - Orco Díaz, Alipio (2020)
Objective: Explain the incidence of public spending on investments, executed by the different sectors (functions), in the level of regional poverty in Peru, 2009-2018 period and propose an econometric model that explains the variability of the level of poverty in function to changes in public spending according to sectors. Method: The research is quantitative, non-experimental, longitudinal panel, descriptive and explanatory. The sample size is confirmed by the 24 regions of Peru, without taking into account the constitutional province of Callao, during the period 2009-2018. Therefore the sample is equal to the product of the 24 regions for the 10 years of the analysis period, this is 240 observations. The program used was the statistical program STATA version 14 due to its versatility, varied statistical tools and the diversity of commands for the analysis of panel-type database. Results: The results show that public spending on investments had an impact on the level of regional poverty, during the period 2009-2018. Likewise, of a total of twelve functions or sectors that make up public spending, seven functions or sectors: agriculture, communications, environment, sanitation, housing, health and education; they have coefficients with negative signs, which correspond to what is theoretically expected. Conclusions: It is concluded that the estimated econometric model as a whole explains 43.23% of the variability in the level of regional poverty in Peru and that investments in environmental, sanitation and education functions had a significant impact on poverty reduction in Peru, in the period 2009-2018.